2018
DOI: 10.2340/00015555-3009
|View full text |Cite
|
Sign up to set email alerts
|

Carvone Contact Allergy in Southern Sweden: A 21-year Retrospective Study

Abstract: Carvone (l-carvone), a mint flavour in spearmint oil, is considered a mild skin sensitizer. Carvone-sensitization may be linked to oral/perioral signs and oral lichen planus, but studies are sparse. The prevalence of patch test reactions to carvone and relevant findings from the positive group were investigated. Records for patch-tested patients at the Malmö clinic, for the period 1996 to 2016, were studied. Carvone-positive and carvone-negative patients were compared regarding patch test data from baseline se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 22 publications
(26 reference statements)
6
43
2
1
Order By: Relevance
“…Carvone, a mint flavour in spearmint oil and an oxidation product of d ‐limonene, is considered a mild sensitizer. Sensitization may be linked to oral or perioral signs, although studies are sparse 22. While we cannot draw any reliable conclusion, as these allergens were tested in only one individual patch test centre, further studies are suggested to assess their importance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Carvone, a mint flavour in spearmint oil and an oxidation product of d ‐limonene, is considered a mild sensitizer. Sensitization may be linked to oral or perioral signs, although studies are sparse 22. While we cannot draw any reliable conclusion, as these allergens were tested in only one individual patch test centre, further studies are suggested to assess their importance.…”
Section: Discussionmentioning
confidence: 86%
“…Sensitization may be linked to oral or perioral signs, although studies are sparse. 22 While we cannot draw any reliable conclusion, as these allergens were tested in only one individual patch test centre, further studies are suggested to assess their importance. This study collected data retrospectively over a 2-year period, which the authors recognize is a limitation.…”
Section: Discussionmentioning
confidence: 89%
“…Carvon ( L -Carvon), ein Minzaroma in Spearmint-Öl, gilt als schwacher Hautsensibilisator, wobei Allergien mit oralen/perioralen Anzeichen und oralem Lichen planus in Verbindung gebracht werden. In einer Klinik in Malmö hatten 147 von 4.221 zugewiesenen Patienten einen positiven Epikutantest auf Carvon; bei 73 % lagen orale Krankheitszeichen vor und bei 57 % oraler Lichen [87]. Bei einer spanischen Patientin wurde eine Sensibilisierung auf das in ihrer Zahnprothesen-Haftcreme enthaltene Cinnamal festgestellt [88].…”
Section: Ergebnisseunclassified
“…Carvone (L-carvone), a mint flavour in spearmint oil, is considered a weak skin sensitizer, allergy being linked to oral/perioral signs and oral lichen planus. In the Malmö clinic, 147 out of 4221 referred patients had a positive patch test to carvone; 73% had oral signs and 57% had oral lichen [87]. A Spanish patient was found sensitised to cinnamal present in her denture fixative cream [88].…”
Section: Fragrancesmentioning
confidence: 99%